Interferons in Traumatic Brain and Spinal Cord Injury: Current Evidence for Translational Application - Roselli, Francesco; Chandrasekar, Akila; Morganti-Kossmann, Maria C. (Frontiers in Neurology, 2018)
This review article provides a general perspective of the experimental and clinical work surrounding the role of type-I, type-II and type-III interferons (IFNs) in the pathophysiology of brain and spinal cord injury. Since IFNs are themselves well-known therapeutic targets (as well as pharmacological agents), and anti-IFNs monoclonal antibodies are being tested in clinical trials, it is timely to review the basis for the repurposing of these agents for the treatment of brain and spinal cord traumatic injury. Experimental evidence suggests that IFN-α may play a detrimental role in brain trauma, enhancing the pro-inflammatory response while keeping in check astrocyte proliferation; converging evidence from genetic models and neutralization by monoclonal antibodies suggests that limiting IFN-α actions in acute trauma may be a suitable therapeutic strategy. Effects of IFN-β administration in spinal cord and brain trauma have been reported but remain unclear or limited in effect. Despite the involvement in the inflammatory response, the role of IFN-γ remains controversial: although IFN-γ appears to improve the outcome of traumatic spinal cord injury, genetic models have produced either beneficial or detrimental results. IFNs may display opposing actions on the injured CNS relative to the concentration at which they are released and strictly dependent on whether the IFN or their receptors are targeted either via administration of neutralizing antibodies or through genetic deletion of either the mediator or its receptor. To date, IFN-α appears to most promising target for drug repurposing, and monoclonal antibodies anti IFN-α or its receptor may find appropriate use in the treatment of acute brain or spinal cord injury.